REGISTRATION OF PATIENT APPLICATION IN CLINIC - Evylia Kartiasari (Jurnal Sistem Informasi, 2010)
The use of computers is now almost penetrated all sectors of human life.Computerization (application of computer technology) not only affect someonepersonally, but also affect people and organizations that exist, do not miss to notbe touched by computerization. The speed and accuracy of the computer is veryuseful in data processing in various applications in different areas, namely toprovide information quickly, precisely and accurately. Registration system isnot computerized at the clinic can often cause such delays that produced theinformation, especially reports on the need. This causes the need to use thecomputer as a tool in data processing and report on a clinic.